2019
DOI: 10.1038/s41375-019-0654-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic T-cell receptor diversity at 1 year following allogeneic hematopoietic stem cell transplantation

Abstract: After allogeneic hematopoietic stem cell transplantation (HSCT), immune reconstitution leads to the development of a new T-cell repertoire. Immune reconstitution could be influenced by events such as conditioning, infections and graft versus host disease (GVHD).Factors influencing the TCR diversity are of great interest to fine-tune the strategy for donor selection and to optimize standard of care. In this work, immunosequencing of the TCR CDR3β region was carried out in a large cohort of 116 full chimeric rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 64 publications
(64 reference statements)
3
31
1
Order By: Relevance
“…Indeed, the primary objective of this study was to evaluate whether a more direct measure of T cell clonal diversity (as measured by high-throughput sequencing) was correlated with clinical outcome, in particular an increased risk of mortality during the first year posttransplant in patients undergoing myeloablative CBT. Differently than our study, Buhler et al recently showed that TCR diversity was not predictive of GVHD, relapse, death, or infections post-HCT in a cohort of 116 donor/recipient pairs undergoing an allogeneic HCT (unrelated = 42; related = 70; haploidentical = 4) ( 25 ). However, the latter study analyzed TCR diversity shortly before transplantation (time point 1) and at 1-year post-HCT (time point 2).…”
Section: Discussioncontrasting
confidence: 97%
“…Indeed, the primary objective of this study was to evaluate whether a more direct measure of T cell clonal diversity (as measured by high-throughput sequencing) was correlated with clinical outcome, in particular an increased risk of mortality during the first year posttransplant in patients undergoing myeloablative CBT. Differently than our study, Buhler et al recently showed that TCR diversity was not predictive of GVHD, relapse, death, or infections post-HCT in a cohort of 116 donor/recipient pairs undergoing an allogeneic HCT (unrelated = 42; related = 70; haploidentical = 4) ( 25 ). However, the latter study analyzed TCR diversity shortly before transplantation (time point 1) and at 1-year post-HCT (time point 2).…”
Section: Discussioncontrasting
confidence: 97%
“…Donors and pre-transplant recipients' repertoires were the most distant. This is in accordance with the findings of Buhler et al,(2019) (40), who studied a large cohort of 116 full chimeric recipients and their respective HSC donors pre-transplant and at 1 year post-transplant. The recipients' repertoire one year post transplant was very different from the donors', with only a few overlaps.…”
Section: Discussionsupporting
confidence: 93%
“…The recipients' repertoire one year post transplant was very different from the donors', with only a few overlaps. This finding led them to suggest that a new repertoire can be reconstituted at any age through thymic dependent or independent pathways (40).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a larger number of patients was analyzed and results indicated that shared TCRs were common within allo-SCT recipients with CMV reactivation. These data were consistent with data from the previous study which reported that repertoire overlap was significantly driven by CMV but otherwise remained markedly limited 39 . Although frequency of shared TCRs and the number that is shared can depend on cohort size and sampling depth 40 , the higher frequency of shared clonotypes and markedly similar CDR3 sequences observed suggested that they may play important roles.…”
Section: Discussionsupporting
confidence: 92%